PENINGKATAN DAN PENGEMBANGAN FASILITAS RUMAH TAHFIZD AL-MAHIRAH DI KELURAHAN TANGKERANG SELATAN KOTA PEKANBARU - Eka Komalasari; Nurmasari; Dia Meirinasuri (Yayasan Wayan Marwan Pulungan, 2023)
This service is entitled: Improvement and Development of Al-Mahirah Tahfizd House Facilities in South Tangkerang Village, Pekanbaru City. This service aims to identify the problems and needs of the Tahfizd Al-Mahirah House in Pekanbaru City, provide solutions based on the identification of problems that exist in the Tahfizd House, and improve the facilities of the Al-Mahirah Tahfizd House in Pekanbaru City to become a quality tahfizd house. The method used has three stages; namely, the discussion is used to find out partner problems and provide solutions that are by partner conditions, observation is used to observe conditions at Rumah Tahfizd, direct practice is used to overcome problems directly, such as providing funding and providing teaching and learning facilities. The results of this service activity are a form of support for the improvement and development of the Tahfizd Al-Mahirah House. The service team assists with learning media facilities and also provides financial assistance that can be used for existing purposes at the Tahfizd Al-Mahirah House.